Counseling and Providing Motivation for Students of State Vocational High School 3 Medan About Professional Health Workers With Global Competitiveness - Aritonang, Barita; Widyaningsih, Fadlilah; Harahap, Hasni Yaturramadhan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Tri Dharma is three obligations at the Lubuk Pakam Medistra Health Institute (Inkes MLP) which include education, research, and community service. Every lecturer at Inkes MLP is responsible for realizing and implementing the Tri Dharma of Higher Education, one of which is community service (PKM). The PKM activities carried out by MLP Inkes lecturers aim to motivate Medan 3 Vocational High School students about professional health workers who are globally competitive at the national and international levels. This activity was attended by teachers and student participants at SMKN 3 Medan, especially grade 12 students who had completed their education. This PKM activity includes initial preparation, delivery of material, counseling and motivating students of SMKN 3 Medan about professional health workers who are globally competitive at the national and international levels. In delivering the material, the PKM team explained that MLP Inkes organizes a quality teaching and learning process so that it has produced many professional health workers and places their graduates to work in health institutions, both in hospitals, health centers, and other health industries and sends graduates to work in abroad, such as in Japan, Germany, Saudi Arabia, and so on. This PKM activity succeeded in providing direct information regarding the profession of professional health workers who are globally competitive at the national and international levels to students of SMKN 3 Medan who will complete their education (graduates) and are interested in continuing to higher education as shown by the enthusiasm of the activity participants in asking several questions to MLP Inkes lecturer.